Malaysian carbon reduction and environmental sustainability tool (MyCREST) qualified - Mohd Firdaus Mustaffa Kamal (Tanjong Malim, 2019)
Malaysian carbon reduction and environmental sustainability tool (MyCREST) qualified by Mohd Firdaus Mustaffa Kamal